P583 The prevalence of side effects to immunomodulators and biologics in patients with Crohn's disease intestinal failure compared with Crohn's disease without intestinal failure. (15th January 2020) - Bouri, S; Geldof, J; Willsmore, J; Donnelly, S; Gabe, S; Hart, A
Abstract: Background: Treatment of Crohn's disease (CD) involves medications and surgery but experiencing medication side effects (SE) limits medical options. The aim of this study was to compare SE experienced by patients with CD and intestinal failure (CD-IF) vs. CD without IF as this may contribute to a higher surgical requirement. Methods: A single tertiary centre retrospective analysis was performed on CD-IF patients on parenteral nutrition due to short-bowel syndrome vs. small bowel CD without IF. Patients with CD without IF were selected from consecutive clinics who lived in the local catchment area. Results: 94 CD-IF and 94 CD patients were included. The proportion of female patients was 56.4% (CD-IF) and 46.8% (CD); mean age was 51.2 (CD-IF) and 41.5 years (CD); mean duration of disease 24 years (CD-IF) and 16 years (CD). Most CD-IF patients had multiple resections. In the CD group, 50 patients never had surgery, 22 had 1 resection, and 9 had 2 or more. From the past medication history for these patients, the proportion in whom a medication was stopped due to SE was similar for CD-IF and CD for azathioprine, mercaptopurine and vedolizumab (Table 1). There were no SE to ustekinumab. Patients in the CD-IF group had a preceding history of significantly more SE to anti-TNF therapy and methotrexate were observed in CD-IF group, of which allergies were most frequent. In the CD group, 2 patients previously had an allergic reaction to infliximab whereas, in the CD-IF group 6 patients had a history of anaphylaxis and 5 an allergy to infliximab, 1 had an allergy to adalimumab and 3 to methotrexate (Table 2). Data on drug levels amongst those with allergy events were limited (due to prior availability of testing); of those tested, 1 had positive antibodies and 1 did not. The frequency of non-response and loss of response was similar between the two groups for each medication. Conclusion: The frequency of SE to immunomodulators and biologics was similar between CD and CD-IF, except for anti-TNF therapy and methotrexate due to more allergy/anaphylaxis events in CD-IF. The frequency of these reactions may have caused an earlier shift towards surgical treatment. 92/94 CD-IF patients were diagnosed prior to 2014; it would be useful to review the incidence of CD-IF before 2014 (pre-vedolizumab and ustekinumab) vs. the new biological era.